2014
DOI: 10.1038/aps.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

RIP3 overexpression sensitizes human breast cancer cells to parthenolide in vitro via intracellular ROS accumulation

Abstract: Aim: Receptor-interacting protein 3 (RIP3) is involved in tumor necrosis factor receptor signaling, and results in NF-κB-mediated prosurvival signaling and programmed cell death. The aim of this study was to determine whether overexpression of the RIP3 gene could sensitize human breast cancer cells to parthenolide in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…1 a). Parthenolide, which can induce cell necrosis through reactive oxygen species (ROS) generation, was used as a positive control in the in vivo test [ 9 , 14 , 15 ]. After administration (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…1 a). Parthenolide, which can induce cell necrosis through reactive oxygen species (ROS) generation, was used as a positive control in the in vivo test [ 9 , 14 , 15 ]. After administration (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of parthenolide with the plasma membrane led to membrane rupture and resulted in rapid necrotic cell death [ 308 ]. Intriguingly, parthenolide-mediated necrosis in human breast cancer MDA-MB231 cells was reduced by NAC and NEC-1, implying the role for activation of ROS and RIPK-1 in these processes [ 309 ]. Furthermore, parthenolide was found to inhibit the NF-κB activity associated with necrosis in multiple myeloma via targeting TNF receptor associated factor (TRAF)-6, as indicated in [ 310 ].…”
Section: Necroptosis Signaling Pathways Cancer and Natural Compoundsmentioning
confidence: 99%
“…In ischemia-reperfusion injury, NF-κB activators phosphorylate the IκB protein, leading to rapid degradation of the IκB protein through the ubiquitin-proteasome pathway and NF-κB nuclear translocation [33]. RIP3 overexpression also activates the NF-κB signal pathway [34,35]. Published studies have shown the contribution of p38MAPK/NF-κB signaling to necroptosis in cardiomyocytes and other cells [36][37][38].…”
Section: Discussionmentioning
confidence: 99%